Heterogeneity of PD-L1 expression and CD8 lymphocyte infiltration in metastatic colorectal cancer and their prognostic significance. Issue 2 (February 2023) - Xin, Haisong; Zhou, Chaoxi; Wang, Guanglin; Liu, Yan; Zhang, Juan; Liu, Youqiang; Li, Baokun; Zhang, Jianfeng; Su, Mingming; Li, Zhihan; Wang, Guiying
Abstract: Purpose: In recent years, immune checkpoint inhibitors have become a major therapeutic method for the treatment of metastatic colorectal cancer (mCRC). Growing evidence indicates that tumour-infiltrating lymphocytes (TILs) in the tumour microenvironment are a prerequisite for the effectiveness of PD-1/PD-L1 blockade therapy. In this study, we aimed to compare PD-L1 expression and cluster of differentiation 4 (CD4) and CD8 TIL infiltration in primary tumours and paired metastases. Patients and methods: Altogether, 111 patients with mCRC who underwent surgery at our hospital were included. PD-L1, CD4, and CD8 expression were detected by immunohistochemistry in a tissue microarray. PD-L1 expression was assessed using the combined positivity score (CPS), and a score ≥1 was judged as positive. The area proportion of TILs with positive staining ≥10% was classified as "high", while <10% was classified as "low". Results: We observed the discordance of PD-L1 expression between primary tumours and paired metastases in 35/111 (31.5%) patients (κ = 0.137, P = 0.142). This heterogeneity was significantly correlated with discordance of CD8 TIL infiltration between primary tumours and paired metastases (P = 0.003). Compared with corresponding colorectal cancer tumours, lung metastases showed more CD8 TIL infiltration (P = 0.022, median: 8.5% vs. 5.0%), whereas liver metastases exhibited less CD8 TIL infiltration (P = 0.028, median: 3.0% vs. 5.0%). Area proportion of CD4 + and CD8 + TIL infiltration in lung metastases were all higher than those in liver metastases (P = 0.005, median: 15.0% vs. 9.0%; P = 0.001, median: 8.5% vs. 3.0%). Compared with p MMR (MSI-L/MS-S) subgroup, area proportion of CD8 TIL infiltration in primary tumours and CD4, CD8 TIL infiltration in paired metastases were all higher in d MMR (MSI-H) group (P = 0.026, median: 15.0% vs 5.0%; P = 0.039, median: 15.0% vs 9.0%; P = 0.015, median: 15.0% vs 5.0%). Preoperative chemo/radiotherapy may increase CD8 TIL infiltration in primary tumours (P = 0.045, median: 10.0% vs. 5.0%). CD8 TIL infiltration in primary tumours was an independent predictive factor for overall survival (HR 0.28, 95% CI 0.09–0.93, P = 0.038). Conclusion: Heterogeneity in PD-L1 expression and CD8 TIL infiltration was found between primary tumours and paired metastases in mCRC. CD8 TIL infiltration in primary tumours could independently forecast the overall survival of patients with mCRC.